PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBEREDS HEADS TOGETHER ( NHT ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 029 SUNGAI AGAS KECAMATAN KUBU KABUPATEN ROKAN HILIR - Ernita '; Lazim N '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research is motivated by thelack of science learning outcomes ofstudents, with a grade average of 68.83. While the completeness criteria Minimumvalue (KKM) IPA is 65 Among students who were 30 only 15 students whoachieve KKM with classical completeness 50%. This research is ClassroomAction Research (CAR) conducted aiming to improve science learning outcomesElementary School fourth grade students 029 Agas River by implementingcooperative learning model NHT. Data collection instruments in this thesis is thesheet activities of teachers and students and learning outcomes. This thesispresents the results obtained by studying the average learning outcome measures68.83 before rising 12.84% to 77.67 in cycle I. In the second cycle increased by17.20% to an average of 80.67. activities of teachers in the first cycle the firstmeeting of the percentage obtained 55% with unfavorable category, the secondmeeting had become 62.50%. Furthermore, the first meeting of the second cycleactivity score increased by 87.50% of teachers either category, at the secondmeeting increased to 100% with a very good category. The results of the dataanalysis of student activity in the first cycle to 50% with the category is not verygood, at the second meeting of 57.50% In this cycle students already understandthe application of cooperative learning activities with the type of NHT. And thesecond cycle activity score of 77.50% of students increased with both categories.At the second meeting increased to 97.50% with very good category. The resultsof the study at 029 River Elementary School fourth grade gnats prove that theimplementation of cooperative learning model to improve learning outcomes NHTIPA fourth grade students of SDN 029 Agas River.Keywords: Cooperative Type Numbereds Heads Together, Science leaning outcome2